Does metformin influence the insulin-, IGF I- and IGF II-receptor gene expression and Akt phosphorylation in human decidualized endometrial stromal cells? - Capp, Edison; Jauckus, Julia; von Eye Corleta, Helena; Toth, Bettina; Strowitzki, Thomas; Germeyer, Ariane (European journal of obstetrics & gynecology and reproductive biology, 2011)
Objective - To assess the effects of metformin on insulin-, IGF I-, and IGF II-receptor gene expression and Akt phosphorylation in decidualized human endometrial stromal cells (ESC) after stimulation with insulin, IGF I and II. - Study design - ESC were isolated from healthy, regularly cycling women and after two passages decidualized with estrogen/progesterone±metformin. Cells were incubated with insulin, IGF I or IGF II for 1, 5, and 10min to assess Akt phosphorylation by Western blot. To investigate the insulin-, IGF I- and IGF II-receptor gene expression ESC were incubated with insulin, IGF I or IGF II for 6 and 24h. - Results - Insulin- and IGF I-receptor gene expression in ESC changed significantly after incubation with insulin, IGF I or IGF II. This was further augmented in metformin pretreated cells, while IGF II-receptor gene expression changed particularly after pretreatment with metformin. Akt phosphorylation peaked after 5min insulin, IGF I and IGF II stimulation in ESC in both control (control 0.08±0.03 vs. insulin 0.74±0.19, IGF I 0.68±0.22, IGF II 0.53±0.13, p<0.05) and metformin pretreated cells (control 0.03±0.01 vs. insulin 0.75±0.11, IGF I 0.74±0.15, IGF II 0.67±0.09, p<0.005). However, there was no significant difference between the control and metformin pretreated group. - Conclusion - Insulin, IGF I and IGF II lead to changes in their receptor gene expression and induced Akt phosphorylation in ESC. These effects were further highlighted in the presence of metformin.